TERJEMAHAN CERITA ANAK: âAKAI KUTSUâ, âNANATSU NO KOâdan âHATSU YUKI NO FURU HIâ - , PUTRI AGANTI, Santi Andayani S.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final assignment is a translation work of Japanese short stories entitled âAkai Kutsuâ ,âNanatsu no Koâ and âHatsu Yuki no Furu Hiâ byYuu Naoko, Ueyama and Awa Naoko. The stories were chosen for their interesting plot and their readability for children. Their distinctive moral messagesare goodandappropriate for children. Translated work for both stories was never before produced as final assignment. Communicative Translation Method was chosen to best translate the stories. It was chosen to avoid difficulties in understanding the translated work as opposed to using literal word-per-word translation method. This method considers communicative principles, accuracy and efficiency